Modern dance commodification strategy in tourism promotion (Study on the modern dance community in Kupang city) - Victor C. B. Raya; Rolland E. Fanggidae; Apriana J. Fanggidae (Goodwood Publishing, 2020)
Purpose: This study aimed to describe the modern dance commodification strategy in promoting cultural tourism in East Nusa Tenggara Province. Research methodology: The research method used in this research is a qualitative method. Respondents used in this study were 15 people. Data processing was performed using a SWOT analysis. Results: According to the analysis results, the most appropriate strategy for the modern dance community in developing cultural tourism in East Nusa Tenggara is to work together with various parties, create online competitions, innovate with culture, and organize independent events by the dancer community. Limitations: This study only discusses the strategy of the commodification of modern dance in tourism promotion in East Nusa Tenggara. Contribution: This research can become scientific information for students specifically studying tourism. Keywords: Modern dance commodification, Tourism promotion